Investigación de mercado para graduados en la carrera de ingeniería en agronomía, Instituto Tecnológico de Costa Rica, Sede San Carlos - Vega-Alvarado, Estrellita (Instituto Tecnológico de Costa Rica, 2015)
The project consists in a Market Research for Engineering Agronomy School's graduates. The study has the main objective of proposing strategies of approaching between Engineering Agronomy's graduates at Tecnológico de Costa Rica. This project was divided into four steps. The first one described the general aspects, literature review, and the methodology chapter. The second step was about the data collection. The third step was to tabulate the data collection. Finally, the last step was descriptions and analysis of the results. In conclusion, this study determined that the Agronomy’s School must incorporate some courses for their studies plan. Besides, it must implement trainings with graduates. Thus, it was proposed recommendations such as opening of new courses in the study plan, and also to create a commission for the Graduated Day as a strategy of approaching.
Proyecto de graduación (Bachillerato en Administración de Empresas) Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, 2015
Keywords: Estudio de mercados; Egresados; Mercado laboral